Traditional Ecological Knowledge on Mangrove Ecosystem Utilization: Learning from Orang Suku Laut Kongky Strait, Lingga - L.N. Firdaus, L.N. Firdaus; Ma’ruf, Rizki; Elmustian, Elmustian; Suarman, Suarman; Melay, Ridwan (Journal of Educational Sciences, 2019)
Traditional Ecological Knowledge (TEK) has eroded globally, particularly which related to ecology. Even though TEK has been recognized as crucial for a sustainable development perspective. This study aims to explore TEK of Orang Suku Laut (OSL) Konky Strait in Lingga about the utilization of mangrove ecosystem. Research area is Konky Strait which is a part of Lingga Regency, Riau Archipelago Province. Data was collecting by using document study, field study, in-depth interviews, meetings and group interviews, participatory and non- participatory observation techniques. There are at least eight species of flora and 17 species of fauna that are known by OSL in Konky Strait. Taxonomically, flora which has been utilized are classified in 6 families, while fauna consist of 15 families. The types of flora are generally utilized for firewood, building materials, fisheries infrastructure (fishing gear) and traditional medicine for health. While the whole fauna species used as food sources. Almost all mangrove flora parts are used such as trunk, branches, leaves, flowers, fruits, shoots, and roots. It can be concluded that Orang Suku Laut Konky Strait have traditional ecological knowledge in the management of mangrove ecosystems in a sustainable manner.